Envisioning Taiwan : fiction, cinema, and the nation in the cultural imaginary - Yip, June Chun, 1962- (Asia-Pacific., 2004)
June Yip traces the growth and evolution of a Taiwan's sense of itself as a separate and distinct entity by examining the diverse ways a discourse of nation has been produced in the Taiwanese cultural imagination.